2012
DOI: 10.1097/dcr.0b013e3182420953
|View full text |Cite
|
Sign up to set email alerts
|

Population–Based Evaluation of Adenosquamous Carcinoma of the Colon and Rectum

Abstract: Background Information about adenosquamous carcinoma of the colon and rectum is scarce due to its extremely low incidence. Objective To examine the prognostic significance of a histological diagnosis of adenosquamous carcinoma compared to adenocarcinoma of the colon and rectum. Design Retrospective study. Setting California Cancer Regisry data from 1994 through 2004 with follow up through 2008. Patients Surgically treated cases of cancer of the colon and rectum excluding anus with tumor histology of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 18 publications
0
62
0
7
Order By: Relevance
“…These findings were reported in a case series involving 44 patients in whom the youngest patient was 19 years old at the time of diagnosis [7]. Other studies reported a mean age of 65 to 67 years at the time of diagnosis [2][3]. In a study by Masoomi et al, a higher proportion of colorectal ASC cases, when compared to cases of colon adenocarcinoma, presented before the age of 60 (37% versus 22%) [2,10].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…These findings were reported in a case series involving 44 patients in whom the youngest patient was 19 years old at the time of diagnosis [7]. Other studies reported a mean age of 65 to 67 years at the time of diagnosis [2][3]. In a study by Masoomi et al, a higher proportion of colorectal ASC cases, when compared to cases of colon adenocarcinoma, presented before the age of 60 (37% versus 22%) [2,10].…”
Section: Discussionmentioning
confidence: 53%
“…Early studies suggested that the sigmoid colon and rectum are the most common sites of primary colorectal ASC [3]. However, a number of more recent studies have shown the distribution of colorectal ASC to be similar to that of colorectal adenocarcinoma with the right side of the colon being more commonly affected [2,7]. Due to the rarity of the disease, no specific pattern of patient presentation or predictors of clinical outcomes have been identified to date.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations